2022
DOI: 10.3389/fcell.2022.819726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2D and 3D Culture Microenvironments on Mesenchymal Stem Cell-Derived Extracellular Vesicles Potencies

Abstract: Therapeutic benefits of mesenchymal stem cells (MSCs) are now widely believed to come from their paracrine signalling, i.e. secreted factors such as cytokines, chemokines, and extracellular vesicles (EVs). Cell-free therapy using EVs is an active and emerging field in regenerative medicine. Typical 2D cultures on tissue culture plastic is far removed from the physiological environment of MSCs. The application of 3D cell culture allows MSCs to adapt to their cellular environment which, in turn, influences their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 62 publications
4
36
0
3
Order By: Relevance
“…Critically in the EV field, recent studies comparing 2D and 3D culture ‐derived EVs have demonstrated culture condition –dependent impact in the EV properties including size (Rocha et al., 2018 ; Villasante et al., 2016 ), cargo (Palviainen et al., 2019 , Millan et al., 2021 ; Rocha et al., 2018 ; Thippabhotla et al., 2019 ; Villasante et al., 2021 ), therapeutic potential (Cha et al., 2018 ), secretion efficiency (Palviainen et al., 2019 ; Millan et al., 2021 ; Rocha et al., 2018 ; Thippabhotla et al., 2019 ), and drug‐delivery potential (Liang et al., 2019 ). Predominantly, the 3D cultures as a source of EVs have been seen to be beneficial when compared to 2D, but opposite findings exist (Kusuma et al., 2022 ). This highlights the importance of testing and applying an appropriate in vitro cell culture model for each EV research application, which requires setting up and optimizing novel models.…”
Section: Discussionmentioning
confidence: 99%
“…Critically in the EV field, recent studies comparing 2D and 3D culture ‐derived EVs have demonstrated culture condition –dependent impact in the EV properties including size (Rocha et al., 2018 ; Villasante et al., 2016 ), cargo (Palviainen et al., 2019 , Millan et al., 2021 ; Rocha et al., 2018 ; Thippabhotla et al., 2019 ; Villasante et al., 2021 ), therapeutic potential (Cha et al., 2018 ), secretion efficiency (Palviainen et al., 2019 ; Millan et al., 2021 ; Rocha et al., 2018 ; Thippabhotla et al., 2019 ), and drug‐delivery potential (Liang et al., 2019 ). Predominantly, the 3D cultures as a source of EVs have been seen to be beneficial when compared to 2D, but opposite findings exist (Kusuma et al., 2022 ). This highlights the importance of testing and applying an appropriate in vitro cell culture model for each EV research application, which requires setting up and optimizing novel models.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest that the 3D high-density culture affects EV cargo, however, a direct comparison is needed to confirm these assumptions. It would also be interesting to assess whether the growth conditions affect the function of the EVs as well as their cargo, as recently reported for mesenchymal stem cells [19, 73]. Furthermore we note that although high culture cell viability is recommended for EV preparations in the MISEV2018 guidelines [45], the conditions in the bioreactor system may be more physiologically relevant due to the 3D structure and natural cell turnover which is abundant in tumours.…”
Section: Discussionmentioning
confidence: 66%
“…The observed similarity in angiogenic activity between the flask- and bioreactor-derived MSC EVs were supported by similar cellular uptake of the EVs by HUVECs and comparable surface protein fingerprints ( Figure 6B, D ). Previous works have shown that cell culture conditions (e.g., bioreactor vs. flask or 2D vs. 3D culture) can enhance EV efficacy, alter EV uptake by recipient cells, and change the EV proteome profile [50, 63, 64]. Importantly, proteomic profiling of EVs utilizing the technique used in the current investigation (i.e., MALDI-TOF MS) can be sensitive.…”
Section: Discussionmentioning
confidence: 95%